Altered Food Habits? Understanding the Feeding Preference of Free-Ranging Gray Langurs Within an Urban Settlement - Dasgupta, Dishari; Banerjee, Arnab; Karar, Rikita; Banerjee, Debolina; Mitra, Shohini; Sardar, Purnendu; Karmakar, Srijita; Bhattacharya, Aparajita; Ghosh, Swastika; Bhattacharjee, Pritha; Paul, Manabi (Frontiers in Psychology, 2021)
Urbanization affects concurrent human-animal movements as a result of altered resource availability and land use pattern, which leads to considerable ecological consequences. While some animals find themselves adrift, homeless with the uncertainty of resources resulting from the urban encroachment, few of them manage to survive by altering their natural behavioural patterns, and co-exist with humans. Folivorous colobines, such as grey langur, whose feeding repertoire largely consists of plant parts, tend to be more attuned to the urban high-calorie food sources to attain maximum fitness benefits within the concrete jungle having an insignificant green cover. However, such a mismatch between their generalized feeding behaviour and specialized gut physiology reminds us of the Liem’s paradox and demands considerable scientific attention which could tell us the story behind colobines’ successful co-existence within human settlements. Besides understanding their population dynamics, the effective management of these urbanized, free-ranging, non-human primate populations also depends on their altered feeding preferences, altogether which could lead us to the development of an ecologically sound urban ecosystem. Here, we have used a field-based experimental set up which allows langurs to choose between natural and urban food options, being independent of any inter-specific conflicts over resources due to food scarcity. The multinomial logit model reveals the choice-based decision making of these free-ranging grey langurs in an urban settlement of West Bengal, India, where they have not only learned to approach the human-provisioned urban food items but also shown a keen interest in it. While urbanization imposes tremendous survival challenges to these animals, it also opens up for various alternative options for human-animal co-existence which is reflected in this study, and could guide us for the establishment of a sustainable urban ecosystem in the future.